1958
DOI: 10.1149/1.2428873
|View full text |Cite
|
Sign up to set email alerts
|

Electropolishing Silicon in Hydrofluoric Acid Solutions

Abstract: Silicon is electropolished in hydrofluoric acid solutions if a critical current density is exceeded. Below the critical c.d., silicon dissolution is largely divalent, and a thick solid layer forms. This film is unstable and reacts slowly with the electrolyte to form tetravalent silicon and hydrogen gas. In the electro‐polishing region, silicon dissolution is mainly tetravalent with the formation of a very thin high resistance type of film.Experimental results on the effect of HF concentration, viscosity, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
285
0
9

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 650 publications
(315 citation statements)
references
References 0 publications
11
285
0
9
Order By: Relevance
“…Porous silicon, first produced in the 1950's by Uhlir [32] and Turner [33], has been shown to be a high surface area (180-225 m 2 /cm 3 ) network of channels (20 A to 100 A wide) with crystalline and amorphous regions [34,35]. Such surfaces make excellent substrates for obtaining transmission FTIR spectra from surface species adsorbed on silicon.…”
Section: Methodsmentioning
confidence: 99%
“…Porous silicon, first produced in the 1950's by Uhlir [32] and Turner [33], has been shown to be a high surface area (180-225 m 2 /cm 3 ) network of channels (20 A to 100 A wide) with crystalline and amorphous regions [34,35]. Such surfaces make excellent substrates for obtaining transmission FTIR spectra from surface species adsorbed on silicon.…”
Section: Methodsmentioning
confidence: 99%
“…PL spectra corresponding to samples prepared in each solution with the same anodization conditions, current density (56.5 mA cm -2 ), anodization time (10 min) and resistivity [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] cm, are shown in Figure 3. PL spectrum for sample produced from HF-MeCN solution presented a blue shift peak that may depend on the pore depth and diameter.…”
Section: Resultsmentioning
confidence: 99%
“…These processes cause hydrogen gas evolution, and highly branched microporous structures. 12,13 Also, for the resultant PS layer the structure is highly dependent on the experimental parameters, such as concentration of the HF acid, current density, anodization time, and also, the doping type associated to the carrier concentrations of the silicon wafer. 5,6,8,12 In addition, another parameter that affects the properties of the PS formed layer that has received little attention are the electrolyte additives.…”
Section: Introductionmentioning
confidence: 99%
“…A current is passed through the cell to result in the formation of an anodic film on the surface of the crystal. 17 The layer that is formed on the surface of the crystal is slightly soluble in the electrolytic solution, and therefore slowly dissolves over time to expose new layers of atoms. Using anodic polishing, the researchers at Bell Labs were successful in the preparation of atomically smooth p-type Si surfaces in concentrated solutions of HF if a threshold current density of 0.01 -0.1 A/cm 2 was exceeded on the surface of the crystal.…”
Section: Technological Developments Leading To Photoluminescent Siliconmentioning
confidence: 99%
“…Further studies into the etching mechanism of n-type Si suggested that below a threshold current density, the process was actually causing a thin mesoporous film to form on the crystal surface. 17 At the time, it was determined by electron and X-ray diffraction that the surface was amorphous, and that the outermost layer was made up of divalent Si atoms. It was further concluded that strong UV-illumination would be required in order to polish n-type Si, rather than etch the surface.…”
Section: Technological Developments Leading To Photoluminescent Siliconmentioning
confidence: 99%